PERAN EFIKASI DIRI TERHADAP REGULASI DIRI PADA PELAJARAN MATEMATIKA DITINJAU DARI JENIS KELAMIN - Paramitha Kusumawati; Berliana Henu Cahyani (JURNAL SPIRITS, 2013)
ABSTRACT            The purpose of this study are to find out the role self-efficacy and self regulated learning of mathematics in term gender. The subjects of this study are 166 students at SMA Muhammadiyah 3 Yogyakarta. The methods in this research are interview between teacher and students, observation and test. The instruments used in this research were regulation and self-efficacy scale. Analyzing data were done by Correlation Product Moment and independent sample t-test with SPSS for windows release version 17.0.             The result shows coeficient correlation r = 0,802, p = 0,000 (p<0,05) and r² = 64,4%, 35,6% of self regulated learning was defined by the other factors such as gender, knowledge, motivation, self willingness. Research shows there is a significant positive correlation between self efficacy for self regulated learning at students and there are differences in self regulated learning by gender.Keyword: self efficacy, self regulated learning.